Digital TV, digital switchover and public service broadcasting in Europe - Iosifidis, Petros (Javnost (Ljubljana), 2007)
This paper aims to assess the role the Public Service Broadcasters (PSBs) have played in driving overall digital take-up and therefore bringing forward the likely date of digital switchover across Europe. While pay television has driven the initial uptake of Digital Television (DTV) in Europe, saturation of the pay television market in terms of penetration may be occurring. Attention was focused on the free-to-view market and with the launch of a number of free-to-air services (e.g. the BBC-led Freeview service in the UK in 2002; the France Televisions-led TNT in France in 2005), Digital Terrestrial Television (DTT) in many parts of Europe has turned into a free-to-air platform. The re-direction of DTT towards a primarily free-to-air system in which PSBs have a key role has proved compelling to many households, particularly affluent, older customers, who are skeptical about pay television, as evidenced by Freeviewćs success (more than 7.5 million customers in early 2007). This paper argues that PSBs have played a significant role in enhancing consumer interest in digital services and making the target of prompt analogue switch-off across Europe in 2012 seem achievable.
Keywords: množične komunikacije; informiranje; digitalne komunikacije; digital television; digitalna televizija; stroški; plačevanje; dostopnost